Pelaksanaan Pelatihan Dan Pengembangan SDM Divisi Customer Service Di PT. Bank Lampung KCP Natar - Fitriana Fitriana (Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Meto, 2020)
In banking institutions, there are competent humant resources in their fields. To get the competent human resources, it is necessary to carry out training and deveopment of human resources. One of the efforts made by PT. Bank lampung Natar is routiney carrying out training and human resource deveopment for a employee divisions, especially the CS division given that CS is a front office that directly serves customers. This type of research is field research with the nature of quaitative descriptive research. Prmary data sources are Edwin Mayardo as supervisor and Eka Puji lestari as an employee CS division at PT. Bank lampung KCP Natar. The conclusion in this study is the implementation of HR development training CS division at PT. Bank lampung KCP Natar is held regularly with the aim of satisfying customers or prospective customers by providing quaity services to customers. As for the trainibng and deveompment of HR CS division that is the method of simulation, role playing and job rotation. The type of training and deveompment of HR CS division include skills training and retraining. After attending training and developing HR, CS is expected to satisfy customers or prospective customers by providing high quality services.